Foundational Principles of Task-Based Language Teaching - East, Martin (ESL & Applied Linguistics Professional Series, 2021)
" The Open Access version of this book will be available soon. This book introduces readers to the concept of task-based language teaching (TBLT), a learner-centred and experiential approach to language teaching and learning. Based on the premise that language learners can enhance their second language acquisition (SLA) through engagement in communicative tasks that compel them to use language for themselves, TBLT stands in contrast to more traditional approaches. Accessible and comprehensive, this book provides a foundational overview of the principles and practice of TBLT and demystifies what TBLT looks like in the classroom. Complete with questions for reflection, pedagogical extensions for application in real classrooms and further reading suggestions in every chapter, this valuable and informative text is vital for anyone interested in TBLT, whether as students, researchers or teachers. "